MAPPING THE LANDSCAPE OF CORPORATE UNIVERSITY RESEARCH: A SYSTEMATIC LITERATURE REVIEW WITH IMPLICATIONS FOR PUBLIC SECTOR LEARNING AND DEVELOPMENT - Christofel J A Roringkon; Mala Sondang Silitonga (RADJA PUBLIKA, 2025)
This study explores the relevance and development of Corporate Universities (Corpu) in the public sector, particularly in supporting strategic learning, human resource development, and institutional transformation. The objective of this study is to systematically map the scientific landscape of Corpu studies in public organizations using a Systematic Literature Review (SLR) approach. This study applies the PRISMA 2020 guidelines and the TCCM (Theory–Context–Characteristics–Methodology) framework, with article selection conducted through the Scopus database. A total of 48 articles from 1983 to 2025 were analyzed based on predetermined inclusion and exclusion criteria. The data were processed using VOSviewer for bibliometric mapping and thematic clustering. The results indicate increasing academic interest in Corpu, dominated by publications from the UK, US, Russia, and Indonesia. The review identified two conceptual frameworks: the Learning System Readiness Framework and the Integrated Learning Value Framework (i-LVF), which combines Outcome-Based Management, ADDIE, and Learning Management Systems (LMS) to strengthen Corpu implementation. This study concludes that although Corpu has gained recognition as an innovation in public sector learning systems, its implementation in developing countries remains under-explored and requires further empirical validation.